Features of Erythropoiesis in Long-Tailed Ground Squirrels Urocitellus undulatus at Arousal from Hibernation - Lizorkina, K.; Tarahovsky, Yu. S.; Aksenova, G. E.; Pyatina, K.; Afanasyev, V. N.; Zakharova, N. M. (Journal of evolutionary biochemistry and physiology, 2025)
The present study constitutes a continuation of earlier research on erythropoiesis in hibernating long-tailed ground squirrels ( Urocitellus undulatus ), which revealed morpho functional differences between the bone marrow (BM) of the humerus and femur of animals. It has been suggested that the observed characteristics may be indicative of the inherited adaptation of hibernating animals to significant internal temperature gradients that occur during their periodic awakenings. In order to verify this assumption а comprehensive investigation encompassing the analysis of flow cytometry and histological features of the humeral and femoral BM, complemented by a series of hematological and biochemical blood tests conducted at various stages of the life cycle of nuclear cells, was undertaken. The findings of this investigation revealed that during the arousal, the femoral BM exerts the most significant influence on the formation of a proliferative pool of cells implicated in the process of erythropoiesis. Concurrently, the humeral BM assumes a pivotal role in the maintenance of a polypotent cellular composition. The obtained data have expanded fundamental knowledge of the processes responsible for stable erythropoiesis in hibernating animals under critical conditions of transition from a torpid to a euthermic state.